The effect of asparagine-13 in porcine epidemic diarrhea virus envelope protein on pathogenicity - Zhiwei Li; Zhiqian Ma; Xiaojing Zhao; Yongqi Li; Congsen Zheng; Yang Li; Xuyang Guo; Lele Xu; Zifang Zheng; Haixue Zheng; Shuqi Xiao (Veterinary Research)
Abstract The pathogenesis of porcine epidemic diarrhea virus (PEDV) has not been fully clarified, which seriously hinders the prevention of the disease. The envelope (E) protein of PEDV induces the expression of pro-inflammatory cytokines, but the role of these inflammatory reactions in PEDV pathogenicity is still unknown. In this study, the asparagine at position 13 was found to be crucial to PEDV E protein induced inflammatory response. Exogenously expressing the parent E protein, rather than the E mutant carrying N13A, induces the activation of NF-κB and expression of inflammatory factors, including IL-6, IL-8, and TNF-α. Compared with the parental rPEDV strain, the recombinant strain rPEDV-EN13A exhibited a significantly lower infectious titer and formed smaller plaques. In addition, rPEDV-EN13A induced lower expression of inflammatory factors in vitro and in vivo. The pathogenicity assay shows that the rPEDV-EN13A strain caused diminished fecal PEDV RNA shedding, delayed death time, and milder histopathological lesions to intestinal villi. Our data provide a unique perspective for exploring the pathogenic mechanism of PEDV and a new target for the development of attenuated PEDV live vaccines.